Uma abordagem institucional da carcinicultura do Rio Grande do Norte de 1999 a 2009 - Lopes, Elisete Cristina (2010)
This study analyzes the institucional environment and its changes around the carcinicultora activity in Rio Grande do Norte from the understanding of its trajectory and the macroinstitucional elements micron and that characterizes the activity in the period of 1999 the 2009. In the analysis of the occured institucional changes in the carcinicultura the Guaraíra Estuary is overcome as space reference, located in the eastern coast of the Rio Grande of the North. The analysis proposal has for base the adoption of the conceptual support of the innovative institucionalistas and neoshumpterianas theories, for understanding that these bring complementary and enriching elements that will allow an analysis, not static, but, dynamics of the carcinicultora activity. It was verified that the crisis brought up for the antidumping action, for the problems of the illnesses that had abated the shrimp, for the depreciation of the Real, among others it led to an overturn in the productive conjuncture of market and forced the alteration of the effective institutions. This institucional alteration, goes in the direction to search to take care of the new demands of the carcinicultura that was possible for the solidity of the institucional foundations constructed throughout the thirty previous years and the consequent consolidation of the composed institucional apparatus for rich a mix of organizations, not only for agencies of government, as well as for organizations with social representation